Pampered or pariah: does animal type influence the interaction between animal attitude and empathy? - Signal, T. (Psychology, crime & law, 2018)
Research into the interaction between deliberate harm of animals and potential risk for human directed violence has burgeoned in the past two decades. In light of an underlying premise that attitudes are predictive of behaviour, a number of researchers have examined demographic and personality variables that affect attitudes to, and by extrapolation behaviours towards, animals. One particularly active topic of research in this area is the potential relation between human-directed empathy and attitudes to animals, with researchers consistently finding that those with higher human-directed empathy scores tend to hold more pro-animal welfare attitudes. The current study adds to this literature by evaluating the effect of different animal types (Pet, Pest or Profit) in this overall animal attitude/human-directed empathy relationship with a large (n = 1606), community-based, Australian sample. As anticipated, attitudes towards animals in the Pet category were significantly more pro-welfare than for either Pest or Profit animals and women indicated more pro-welfare attitudes across all three than men. The strength and significance of the relation between human-directed empathy and attitudes to animals varied across Pet, Pest and Profit animal categories and affective vs cognitive empathy. The strongest correlation was found between Pet and the Empathic Concern subscale of the Davis Interpersonal Reactivity Index. The implications of these differences for the previously observed link between attitudes to animals and empathy, humane education and future research directions are discussed.